Pengaruh Training Terhadap Produktivitas Kerja Karyawan Konsultan di Surabaya: (Studi Kasus Pada PT. Asuransi Umum BUMIDA 1967) - Intan Permata Sari; Achmad Daengs GS; Rina Dewi; Bambang Karnain; Harsono Teguh (Jurnal Pengabdian Masyarakat, 2025)
PT. Bumida General Insurance 1967 as a company that wants to continue to grow requires employees who have skills and knowledge that are always updated. Through well-structured training programs, companies can ensure that employees are always ready to face new challenges, both in facing competition and in providing the best service to clients. This is one way to ensure that work productivity is maintained and even increased. This research aims to determine how far the effective implementation of training is related to increasing the work productivity of PT consultant employees. Bumida General Insurance 1967 Surabaya. This research is quantitative research. The research population was all employees of PT. Bumida General Insurance 1967 Surabaya, totaling 55 people. The sampling technique uses saturated sampling so that all employees become the research sample. Data analysis uses linear regression with hypothesis testing using the t test. The research results show that training has a significant effect on employee work productivity. This indicates that the training provided to employees can significantly improve employee performance, which has an impact on increasing company productivity.